qanda-logo
search-icon
Symbol
apple-logo
google-play-logo

Calculator search results

Formula
Solve the equation
Answer
circle-check-icon
expand-arrow-icon
Graph
$y = 4 x - 3$
$y = 3 x + 2$
$x$Intercept
$\left ( \dfrac { 3 } { 4 } , 0 \right )$
$y$Intercept
$\left ( 0 , - 3 \right )$
$x$Intercept
$\left ( - \dfrac { 2 } { 3 } , 0 \right )$
$y$Intercept
$\left ( 0 , 2 \right )$
$4x-3 = 3x+2$
$x = 5$
$ $ Solve a solution to $ x$
$4 x - 3 = \color{#FF6800}{ 3 } \color{#FF6800}{ x } + 2$
$ $ Move the variable to the left-hand side and change the symbol $ $
$4 x - 3 \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 2$
$4 x \color{#FF6800}{ - } \color{#FF6800}{ 3 } - 3 x = 2$
$ $ Move the constant to the right side and change the sign $ $
$4 x - 3 x = 2 \color{#FF6800}{ + } \color{#FF6800}{ 3 }$
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 2 + 3$
$ $ Organize the expression $ $
$\color{#FF6800}{ x } = 2 + 3$
$x = \color{#FF6800}{ 2 } \color{#FF6800}{ + } \color{#FF6800}{ 3 }$
$ $ Add $ 2 $ and $ 3$
$x = \color{#FF6800}{ 5 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple-logo
google-play-logo